Angiogenesis modulates adipogenesis and obesity - Cao, Yihai (American Society for Clinical Investigation, 2007)
Substantial evidence shows that neoplastic and nonneoplastic tissue growth is dependent on angiogenesis. Neovascularization and adipogenesis are temporally and spatially coupled processes during prenatal life and they continue to reciprocally interact via paracrine signaling systems throughout adult life. Activated adipocytes produce multiple angiogenic factors including leptin, angiopoietins, HGF, GM-CSF, VEGF, FGF-2, and TGF-β, which either alone or collectively stimulate neovascularization during fat mass expansion. Thus antiangiogenic agents provide a novel therapeutic option for prevention and treatment of human obesity and its related disorders.